(untitled) (Journal of Philosophy Culture and Political Science, 2021)
This article examines the problem of cognition in Ibn Sina’s falsaf. That is, its theoretical and ideological origins have been analyzed. The purpose of the article is to focus on the problem of perception and the problem of imagination. The process of cognition of Ibn Sina is his interpretation of material as the process of the emergence of things in the world. The process of cognition of a person is interpreted as the process of the appearance of objects in the thinking material world. That is, matter in the mind of the thinker exists as an opportunity and the mind as an active initiative. According to Ibn Sina, the mind is divided into two, it is divine and human. The first is a prerequisite for things, the second follows them. According to the authors that questions of the theory of knowledge, in particular, questions of sensation, are dealt with in an original and independent way by Ibn Sina. So, in explaining the process of vision, Ibn Sina critically examines the views of Plato, Democritus and other ancient Greek philosophers and claims that with our eyes we perceive only the colors of objective things. This sensation occurs by reflecting light from external objects when the light hits them, similar to the reflection of external objects in mirrors. Thus, Ibn Sina considered fantasy and imagination to be various forms of creative cognition, and he connected the content of these forms of human thought through feelings with external reality and sought to find their material substrate in the brain of a living being. Key words: Сognition, theory of knowledge, external feeling, internal feeling, perception, sensation, imagination, fantasy.